2014
DOI: 10.1017/s002531541400006x
|View full text |Cite
|
Sign up to set email alerts
|

Can whale-watching and whaling co-exist? Tourist perceptions in Iceland

Abstract: Both whaling and whale-watching tourism occur in Iceland, but these activities are considered incompatible by many, and previous studies have suggested that whale-watch tourists would boycott whale-watch destinations where whaling takes place. This study assessed the perceptions of and attitudes towards ongoing whaling amongst whale-watch tourists in Iceland. A majority of whale-watching tourists in Iceland did not support whaling and did not think that whale-watching and whaling could exist side by side. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Most empirical studies have determined that whaling and whale watching are perceived as being either incompatible activities or the former has a severely detrimental impact on the latter ( Hoyt & Hvenegaard, 2002 ; Kuo, Chen, & McAleer, 2012 ). This was also the finding of the survey-based study by Bertulli et al (2016) focused on Faxaflói Bay, which found that most tourists did not think whaling and whale watching could exist side by side, a finding which again has potential marine spatial planning implications with regards to the size and scope of the Faxaflói Bay whale sanctuary.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Most empirical studies have determined that whaling and whale watching are perceived as being either incompatible activities or the former has a severely detrimental impact on the latter ( Hoyt & Hvenegaard, 2002 ; Kuo, Chen, & McAleer, 2012 ). This was also the finding of the survey-based study by Bertulli et al (2016) focused on Faxaflói Bay, which found that most tourists did not think whaling and whale watching could exist side by side, a finding which again has potential marine spatial planning implications with regards to the size and scope of the Faxaflói Bay whale sanctuary.…”
Section: Discussionmentioning
confidence: 58%
“…For many centuries, Faxaflói Bay's abundant fishing resources have provided important sustenance and income-generators for the people living on its coastline. In addition, a broad variety of wildlife is present in the Bay, including minke, humpback and fin whales ( Bertulli, Rasmussen, & Tetley, 2013 ), dolphins, harbour porpoises ( Rasmussen & Miller, 2002 ), and puffins ( Bertulli et al, 2016 ). Today, a broad array of economic activities continues to take place in Faxaflói Bay, including fishing, shipping, cruise ship tourism, sailing, whale watching and commercial whaling.…”
Section: Case Study Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…A monetary ES valuation study on the trade-offs between cultural and provisioning whale ES in Iceland found that women were willing to pay more for the expansion of a sanctuary that would limit whaling in the area, as were respondents with higher education (Malinauskaite et al, 2020b). Visitors valued whale meat more than locals, which might be associated with its marketing as a traditional Icelandic food (Bertulli et al, 2016;Huijbens & Einarsson, 2018) and the absence of whaling in the area.…”
Section: Contextualising the Study Results Within The Es Literaturementioning
confidence: 99%
“…There are also possible trade-offs between provisioning and recreational ES in Iceland, as observed by Cook et al (2020) and Bertulli et al (2016). Another trade-off within ES is related to unregulated whale watching and the ES of recreation and tourism.…”
Section: General Findingsmentioning
confidence: 95%